Research priority setting in women's health: a systematic review. (6th April 2020) - Graham, L; Illingworth, BJG; Showell, M; Vercoe, M; Crosbie, EJ; Gingel, LJ; Farquhar, CM; Horne, AW; Prior, M; Stephenson, JM; Magee, LA; Duffy, JMN
Abstract : Background: Developing a shared agenda is an important step in ensuring future research has the necessary relevance. Objective: To characterise research priority setting partnerships (PSPs) relevant to women's health. Search strategy: Included studies were identified by searching MEDLINE and the James Lind Alliance (JLA) database. Selection criteria: Priority setting partnerships using formal consensus methods. Data collection and analysis: Descriptive narrative to describe the study characteristics, methods, and results. Main results: Ten national and two international PSPs were identified. All PSPs used the JLA method to identify research priorities. Nine PSPs had published a protocol. Potential research uncertainties were gathered from guidelines (two studies), Cochrane reviews (five studies), and surveys (12 studies). The number of healthcare professionals (31–287), patients (44–932), and others (33–139) who responded to the survey, and the number of uncertainties submitted (52–4767) varied. All PSPs entered confirmed research uncertainties (39–104) into interim priority setting surveys and healthcare professionals (31–287), patients (44–932), and others (33–139) responded. All PSPs entered a short list of research uncertainties into a consensus development meeting, which enabled healthcare professionals (six to 21), patients (eight to 14), and others (two to 13) to identify research priorities (ten to 15). Four PSPs have published their results. Conclusion: Future research priority setting studies should publish a protocol, use formal consensus development methods, and ensure their methods and results are comprehensively reported. Tweetable abstract: Research published in @BJOGtweets highlights future research priorities across women's health, including @FertilityTop10, @jamesmnduffy. Tweetable Abstract: Research published in @BJOGtweets highlights future research priorities across women's health, including @FertilityTop10, @jamesmnduffy. This paper includes Author Insights, a video abstract available at https://vimeo.com/rcog/authorinsights16150